Phenomenological study on the Ex-pin phenomena in the initial phase of HCDA on metal-fueled SFR using simulant. (August 2019) - Lee, Min Ho; Heo, Hyo; Jerng, Dong Wook; Bang, In Cheol
Highlights: Ex-pin phenomena were experimentally studied with simulant. Correlation for levitation height of the ejected fuel was developed. Accident at the BOC is more serious than that of EOC in terms of levitation. Abstract: In the initial phase of severe accident in a metal fueled SFR, fuel melts and is ejected into the coolant channel owing to pressure from fission gas. This phenomenon called ex-pin and it is crucial for early termination of the accident in terms of levitation, which induces negative reactivity feedback and coolable geometry. The ejected mass of melt, melt temperature, coolant temperature, ejection pressure, and the void generated by coolant boiling in the channel were parametrically studied in experiments designed to determine the influence of each parameter on levitation and coolable geometry. Experiments were conducted using the simulant materials Wood's metal and water for the molten fuel and sodium coolant. For coolable geometry, less amount of fuel was adhered to the channel wall with high coolant temperature and fragmentation of the melt was promoted under high temperature melt, high ejection pressure, and voided channel. The levitation height was mainly affected by the volume of ejected gas and melt. Levitation height model was developed based on the experiments. Considering change of these parameters along fuel cycle, an accident at the beginning of the fuel cycle is more serious than one at the end of the fuel cycle.